Empathic nonverbal behavior increases ratings of both warmth and competence in a medical context - Kraft-Todd, Gordon T.; Reinero, Diego A.; Kelley, John M.; Heberlein, Andrea S.; Baer, Lee; Riess, Helen (PLOS ONE, 2017)
In medicine, it is critical that clinicians demonstrate both empathy (perceived as warmth) and competence. Perceptions of these qualities are often intuitive and are based on nonverbal behavior. Emphasizing both warmth and competence may prove problematic, however, because there is evidence that they are inversely related in other settings. We hypothesize that perceptions of physician competence will instead be positively correlated with perceptions of physician warmth and empathy, potentially due to changing conceptions of the physician’s role. We test this hypothesis in an analog medical context using a large online sample, manipulating physician nonverbal behaviors suggested to communicate empathy (e.g. eye contact) and competence (the physician’s white coat). Participants rated physicians displaying empathic nonverbal behavior as more empathic, warm, and more competent than physicians displaying unempathic nonverbal behavior, adjusting for mood. We found no warmth/competence tradeoff and, additionally, no significant effects of the white coat. Further, compared with male participants, female participants perceived physicians displaying unempathic nonverbal behavior as less empathic. Given the significant consequences of clinician empathy, it is important for clinicians to learn how nonverbal behavior contributes to perceptions of warmth, and use it as another tool to improve their patients’ emotional and physical health.